2015
DOI: 10.1007/s12663-015-0854-6
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Periosteal Dissection with Denture-Guided Epithelial Regeneration: A Novel Method for Peri-Implant Soft Tissue Management in Reconstructed Mandibles

Abstract: Background In patients with reconstructed mandibles using free fibula flaps, management of soft tissues around implants supporting dental rehabilitation, is often a clinical problem. Aim The aim of this paper is to describe a new technique, namely ''Sub-periosteal dissection and denture-guided epithelial regeneration (SD-DGER)'', as a method of periimplant soft tissue management in these patients. Materials and methodsThe technique consists of performing a subperiosteal dissection with creation of buccal and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Peri‐implant soft tissue management was carried out at the time of interim prosthesis loading using the technique of sub‐periosteal dissection with denture guided epithelial regeneration. The above‐mentioned procedure is described in detail elsewhere (Kumar, et al, ; Kumar, Jacob, & Kuriakose, ).…”
Section: Methodsmentioning
confidence: 99%
“…Peri‐implant soft tissue management was carried out at the time of interim prosthesis loading using the technique of sub‐periosteal dissection with denture guided epithelial regeneration. The above‐mentioned procedure is described in detail elsewhere (Kumar, et al, ; Kumar, Jacob, & Kuriakose, ).…”
Section: Methodsmentioning
confidence: 99%
“…3c). Kumar et al have shown the feasibility of the establishment of attached mucosa on the transplanted fibula intraorally (Kumar et al, 2014). Concerning this case, the total recovery time seems to be shorter than the two-stage fibula reconstruction proposed by Rohner et al (Rohner et al, 2002).…”
Section: Discussionmentioning
confidence: 69%
“…These findings suggest that if the soft tissue around the implant is a skin flap, the implant installation for the mandibular reconstruction with fibula-free flap leads to a high risk of inflammation around the implant. When corrective measures to improve the soft tissues were not implemented, poor hygiene around the implants, hyperplastic peri-implant tissue, soft tissue infections and abscesses that start as peri-implant marginal bone loss were all observed, and this may eventually lead to loss of the implant and the dental rehabilitation [ 2 , 11 ]. These results are consistent with the observations reported by Sozzi et al [ 5 ] that suggest the optimal soft tissue around an implant should be immobile, thin, soft, smooth (wrinkle-free) and hairless.…”
Section: Discussionmentioning
confidence: 99%
“…Other widely investigated methods are as follows: (1) Sub-periosteal dissection with denture-guided epithelial regeneration (SD-DGER) [ 2 , 11 ]. This method promotes mucosa formation via dentures, after the removal of the skin flap.…”
Section: Introductionmentioning
confidence: 99%